AN OVERVIEW OF ROLE TIM WORK DIMENSION, ADEQUATE STAFF AND HEALTH WORKERS’ PERCEPTION OF PATIENTS SAFETY CULTURE - Fatmawaty fatma Mallapiang; Hasbi Ibrahim; Nur Fitriyani Arifuddin; Azriful Azriful; Surahmawati Surahmawati (Universitas Islam Negeri Alauddin Makassar, 2021)
Background:Medical error is a threat to every patient who wants to take care, therefore the importance of patient safety culture is applied in every hospital to keep patients safer in terms of health careObjective:This research describes the overview of role teamwork dimension, adequate staffand health workers’ perception of patient’s safety culturein the hospitalization unit of Dr. Tajuddin Chalid Hospital of MakassarMethod: It uses a descriptive quantitative approach to explain the issue. The research samples consist of 107 health workers stationed at the hospitalization unit by utilizing the purposive sampling techniqueResult: The findings show that the patient safety culture falls into a moderate category (57.0%). Teamwork on moderate category 55,1%, adequate staff on moderate category (65.4%), and health workers’ perception of patient’s safety on moderate category (77.6%)Conclusion: This research concludes that the safety culture in the hospitalization unit of Dr. Tajuddin Chalid Hospital of Makassar is classified moderate, signifying that the health workers have practiced the patient safety culture by the Patient Safety Standards (PSS) despite some lacking in several areas. It also encourages following the SOP by conducting training and workshops for the health workers.